The Persistency Of International Diversification Benefits: The Role Of The Asymmetry Volatility Model - Ung , Sze Nie; Choo , Wei Chong; Sambasivan, Murali; Md. Nassir, Annuar (Asian Academy of Management (AAM), 2014)
This study restates the issue of international portfolio diversification benefits by considering the problem of perfect foresight assumption and constant variancecovariance estimation. Whilst emphasising the role of the asymmetry volatility model in portfolio formation, we also investigate the economic implication of the smooth transition exponential smoothing (STES) method in portfolio risk management. Our results suggest that all portfolios perform better in the ex-post period compared to the ex-ante period. However, investors may not be able to obtain any benefits from diversifying their portfolio in developed stock markets in both ex-ante and ex-post periods. Further investigation on the economic implications of the STES method also show that the STES method does help to cushion losses generated from the international diversification portfolio. Hence, this suggests the use of the STES method in computing and monitoring the risk of an internationally diversified portfolio.